Formação continuada para professores: uma prática possível na elaboração de consignas da produção textual - Silva, Similaine Sibeli da (2016)
When we teachers ask in classroom a writtentext production, we use in some sort of guidance general oral or written that this research we are calling the slogan. Based on the information contained in the slogan, students will plan, write and revise their texts with a view to cater to what was requested. Thus, the slogan has an important role in writing the production process. Based on this understanding, we proposed a study whose themes are the slogans for the production written in the Early Years of elementary school, from the perspective of discursive / textual genres. We defend the idea that this schooling stage, in which students are starting their schooling writing practices, greater clarity have about what we are requesting, the greater the possibilities of producing texts that address and meaningful. Based on this understanding, this work has been guided by two questions: "How are characterized the slogans used in schools in a city in northwestern Paraná?" And "What effects a course of continuing education for teachers in the early years of schooling produces in its understanding on the role and the development of slogans to produce writing in school? ". In order to find the answer (s) to this questioning, from slogans of test results collected in the second half of 2013, in which we investigate its themes, compositional structure and linguistic style, was promoting a continuing education course for Teachers Years Basic Education Initial context researched, whose aim was to analyze its effects on the development of slogans by the participants. At perspective to achieve the proposed objective, we rely on the perspective of Bakhtin studies on language, language, discourse genres and text, with the main theoretical frameworks Bakhtin (2003); Bakhtin / Voloshinov (2006); Geraldi (2013); Dolz, Gagnon and Decandio (2010); Brazil (1997); Parana (2010), among others. Methodologically, it is a guided research in Applied Linguistics of the framework (MOITA LOPES, 1996; RODRIGUES, CERUTTI- RIZZATTI, 2011), qualitative kind, using the ethnographic approach, through action research, made up of two stages: first (and raising slogans analysis), data were generated from a sample containing 83 slogans used by teachers and students. The results obtained at that time provided information for planning and the preparation of the second stage: completion of a course of continuing education for teachers, addressing the theme of this research. At that moment there was action research, whose generation data constituted by the slogans they have developed during the course. The survey data showed that at first the results presented to the teachers were striking, and with the training course could take a different stance on the text production of teaching because most teachers could suit the slogans to the conditions of production.